Emotional Intelligence as a Medium to Improve the Learning Achievement of Students at MI Raudlatul Ulum Bojonegoro - M. IQBAL TAWAKKAL (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The issue of low academic achievement among students at MI Raudlatul Ulum Bojonegoro is influenced not only by cognitive factors but also by non-cognitive aspects such as difficulties in managing emotions, low self-confidence, and limited learning motivation. This study aims to analyze the role of emotional intelligence as a medium for improving students’ academic achievement, focusing on self-awareness, emotional regulation, and the development of positive social interactions. Employing a qualitative approach with a case study design, this research involved students, classroom teachers, and homeroom teachers as key informants. Data were collected through observations, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings reveal that students with higher emotional intelligence are more capable of managing anxiety during learning activities, maintaining concentration, and developing intrinsic motivation, all of which significantly contribute to better academic performance. Additionally, students’ empathy and effective communication skills were found to foster cooperative behavior and create a more conducive classroom environment. Theoretically, this study reinforces the importance of emotional intelligence as a key determinant of learning success. Practically, it highlights the need for integrating emotional intelligence development into learning strategies through teacher guidance, positive behavioral habituation, and strengthening socio-emotional competencies to optimally support improvements in students’ academic achievement.